An anchored matching-adjusted indirect comparison of fixed-dose combination calcipotriol and betamethasone dipropionate (Cal/BDP) cream versus Cal/BDP foam for the treatment of psoriasis. (17th November 2022) - Bewley, Anthony; Barker, Erin; Baker, Hannah; Green, Will; Avey, Brooke; Pi-Blanque, Aina; Galván, Jordi; Trebbien, Paw; Praestegaard, Morten
Abstract: Objectives: To undertake a comparison of Cal/BDP cream versus foam for the treatment of plaque psoriasis, with cross-trial population differences accounted for. Materials and Methods: An anchored matching-adjusted indirect comparison was undertaken, using individual patient data for Cal/BDP cream and published aggregated data for Cal/BDP foam. Altogether, 11 outcomes were analyzed, including PGA success, mPASI75, DLQI-related outcomes and treatment satisfaction across numerous domains. For each outcome an odds ratio or mean difference was calculated to represent the relative efficacy of Cal/BDP cream versus foam. Methods were guided by NICE Decision Support Unit recommendations. Results: After adjustment, baseline characteristics were balanced across treatment arms in each analysis. There were no statistically significant differences in PGA success, mPASI75 or DLQI outcomes between Cal/BDP cream and foam when they were compared after their recommended treatment durations (8 weeks for cream and 4 weeks for foam). For treatment satisfaction after 1 week of treatment, Cal/BDP cream was significantly superior to the Cal/BDP foam in all but one domain of the questionnaire. Conclusions: Cal/BDP cream and Cal/BDP foam have equivalent efficacy and HRQoL (measured in DLQI) outcomes when used for the topical treatment of plaque psoriasis at their recommended treatment durations. A comparison of treatment satisfaction assessments after 1 week of treatment demonstrated that patients find Cal/BDP cream to be more convenient than foam.